Distinct roles of claws and adhesive pads in honey bees determine their adhesive performance under varying surface roughness conditions through a dual-mode synergistic adhesion mechanism. - Youhe Yu; Hongqi Luo; Yongxia Gu; Jieliang Zhao (PLoS ONE)
Surface roughness is a critical factor that affects surface adhesion in bees. Investigating the mechanisms underlying surface adhesion in bees on substrates with varying surface roughness levels provides a theoretical basis for designing bioinspired adhesives and micro-climbing robots. In this study, a specialized adhesion measurement device was developed to compare the adhesive forces applied on substrates with different roughness levels by intact bees and by those whose adhesive pads have been removed. Moreover, a contact model for adhesion between the claw tips and substrate particles and a liquid bridge model for adhesion between the adhesive pads and substrate surfaces were established to analyze the distinct roles of claws and adhesive pads, respectively, under different surface roughness conditions. The results revealed that on surfaces with roughness values below 3.2 μm, the adhesive pads secreted liquid to form liquid bridges, increasing contact area and adhesive force, thereby dominating the adhesion process. As the surface roughness increased, the contribution of the adhesive pads diminished, whereas the mechanical interlocking effect of the claws became relatively more pronounced. When the surface roughness exceeded 36 μm, the irregularity of substrate particles enhanced the interlocking effect of the claws, making the force generated by the claw tip the dominant adhesion force. Thus, the integration of the contact and liquid bridge models revealed the synergistic effects of mechanical interlocking and liquid bridge mechanisms on improvement in surface adhesion in bees.